Internal Control Model for Woman Cooperatives in Indonesia: A Case Study - Chuldun, Ibnu; Rokhman, Fathur; Pramono, Suwito Eko; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2024)
Woman cooperatives play essential roles in empowering women. Woman cooperatives have different characteristics from others. It is held in every village, coordinated by a woman. The study objectives are to design quality improvement wildly internal control for woman cooperatives entity. The study provides case studies of the organizational financial management practices of 17 woman cooperative entities reform in Indonesia. The empirical methods are analyzed and interpreted within internal control activities. Accordingly, we recommended the pattern of new member acceptance by a selective orientation of potential candidates for productive enterprises: the transparency rules and operational procedures for both savings and loans, ongoing reporting with adequate monitoring. The woman cooperatives also must have standard operating procedures and standard operational management. The development of women entrepreneurship in emerging economies may continuously face challenges, particularly in countries with multicultural attributes. This research needs further to explore the great potential of women entrepreneurship in Indonesia, increasing support for women’s entrepreneurial activity, improving their chances of success, and generating more value for society.